2019
DOI: 10.3390/nu11020387
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Association of Skipping Breakfast with Weight and Cardiometabolic Risk Factors in Children and Adolescents. What Should We Better Investigate in the Future?

Abstract: The incidence of skipping breakfast in pediatric subjects is rising, and a relationship with overweight (OW) and obesity (OB) has been shown. Associations with cardiovascular outcomes and skipping breakfast in adults have been reported. The purpose of this systematic review was to summarize the association of skipping breakfast with body weight and metabolic outcomes in the pediatric population. We searched relevant databases (2008–2018) and identified 56 articles, of which 39 were suitable to be included, bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

38
204
1
16

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(259 citation statements)
references
References 66 publications
38
204
1
16
Order By: Relevance
“…25 These are well-known risk factors for developing overweight and obesity in children and adolescents. [26][27][28][29] Interestingly, these behavioral characteristics were more common among high school students, which is in line with the rapidly increased prevalence of obesity in the same population group.…”
Section: Characteristics Of Obesity In Korean Children and Adolescentssupporting
confidence: 61%
“…25 These are well-known risk factors for developing overweight and obesity in children and adolescents. [26][27][28][29] Interestingly, these behavioral characteristics were more common among high school students, which is in line with the rapidly increased prevalence of obesity in the same population group.…”
Section: Characteristics Of Obesity In Korean Children and Adolescentssupporting
confidence: 61%
“…Many previous studies have reported an association between skipping breakfast and evening type (27,44,45). Skipping breakfast is unhealthy eating behavior which contributes to metabolic disorders including obesity and diabetes (46,47). In the present study, skipping lunch and dinner was associated with chronotype as well as skipping breakfast.…”
Section: Discussionsupporting
confidence: 48%
“…48 According to a systematic review, the prevalence of skipping breakfast ranged from 10% to 30%, with an increasing trend in adolescents, mainly in girls, which was associated with a worse lipid profile, worse blood pressure, and metabolic syndrome. 49 Although the mechanisms underlying the adverse effect of skipping breakfast are unclear, they might be related to inadequate intake of certain foods and might induce some degree of nutritional defect in the morning. For instance, low dietary intake of some fibercontaining foods and dairy products was found to be inversely correlated with menstrual pain.…”
Section: Discussionmentioning
confidence: 99%